LCC113: English for Communicative Competence III - UiTM, Academy of Language Studies (2023)
This course is designed to develop students’ receptive, productive, and interactive skills. It is aimed for them to be confident and independent users of the language, equipping them with the necessary skills to discuss arguments and issues effectively. It focuses on enhancing the students’ abilities to use the language by exploiting a variety of materials in varied situations. This is done through the integration of the language skills (reading, speaking, writing) from CEFR B2 (low) to B2 (high).